The Simple Machines for Making Organic Fertilizer at School - Suyanto, Beny; Sigit, Prijono (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Bio organic manure is fertilizer made from organic material (plants, animal dungs etc.) as a source of nutrient for plants. How to produce was using a simple technology, the material needed was Effective Microorganism (EM ) as biodecomposter in fermenting organic material. The purpose of the study was to design a tool to make organic manure. The source of green manure was grass and leaves taken from the School of Environmental Health âMagetanâ, Health Polytechnic of Surabaya. The process of appropriate technology starts from copping the material (Â±1 cm), using 7 Pk cutting box copper, the raw material was suitable enough for the raw material of organic fertilizer. The next step is to drum the material into a digestor as a composter. To reduce the time needed for composting, it was needed additional material EM4 (Effective Microorganism) in 3 variation namely 2%, 4% and 6% with duration of 14 and 21 days. The assessment of  the maturation of the organic manure based on the smell, colour, texture, pH, temperature and the result of laboratory test N, P , K C/N ratio with the duration of  the fermentation process varied between 14 and 21 days. The nutrient content reference refers to SNI/2004. Result of the study about kind of garbage: grass and bushes leaves with the capacity of 5 to 20 kg/day. Tool specification mechanic chopper box consists of two components mover motor (7 PK) and box chopper (leave cutter). Digestor specification: 1 unit of iron wagon frame, 1 unit of digestor, the process of fermentation using EM4. The result of observation and measurement of temperature, pH, moisture, colour, smell, texture and grade C, N, P, K and C/N ratio qualifies SNI/2004. Fermentation process EM 2% within 14 to 21 days was the efficient result in cmpost maturation. The suggestion in this research, a further study is needed to increase the useful mechanic box chopper capacity and granulator design development to process compost into worthy compost granule, cheap MOL production, local materialand the result is better than EM4.